Parijat: A tree from Heaven with Confused Identity on the Gods’ Earth - Jha, Kaushalendra Kumar (Indian Forester, 2021)
In the present context, two trees, Harshringar and Baobab, are in contention for being established as Parijat, a tree from heaven revered by Hindus, based on cultural practices as well as available evidence in literature. The former is indigenous while the latter is of African origin. The faith in Harshringar has existed longer than the introduction of the exotic Baobab which has some official credentials to its credit. The lack of clarity needs to be addressed based on further research on the topic.